Percepção de suporte familiar: autoeficácia e qualidade de vida em estudantes de psicologia. - Silva, Rosana Rodrigues da (2019)
The perception of family support is related to the level of support given by the family in order to meet the needs of its members, being pointed out as a pillar of people's psychic life. The belief that the individual has in his ability to achieve his goals in life, his self-efficacy, will be partly based on the interpersonal relationships that he establishes since childhood, whether in the family, social or academic environment of which he is a part. In turn, quality of life implies how the individual assesses his position in life, in the context of culture, as well as, his goals, expectations and values. This research investigated the relationship established between the perception of family support, self-efficacy and quality of life of psychology students. This is a quantitative cross-sectional study, using four instruments: Sociodemographic Questionnaire, Family Support Perception Inventory, Perceived General Self-Efficacy Scale and the WHOQOL-BREF in a sample of 200 students, both male and female, older 18 years old, from the Psychology course of a private higher education institution in the city of Recife - PE. Data collection was carried out collectively in an appropriate environment and followed all required ethical precepts. The results showed that 85% of the sample is female, 76.5% are between 18 and 25 years old, 86.4% are single and 56.1% have parents who are not separated. With regard to quality of life, it was found that the highest median was obtained in the Psychological domain and that most students consider having a low perception of self-efficacy and family support with a higher prevalence of this perception in separated and male students. There was a correlation between perceived quality of life, family support and perceived self-efficacy. These results suggest the need to think about actions that reflect, satisfactorily, on the quality of life and the professional performance of psychology students.